Lack of correlation between periodontitis and renal dysfunction in systemically healthy patients - Brotto, Renata Squariz [UNESP]; Vendramini, Regina Célia [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP]; Ramos, Adriana Pelegrino Pinho; Pepato, Maria Teresa [UNESP] (My University, 2011)
Objectives: The aim of this study was to assess a suggested association between periodontitis and renal insufficiency by assaying kidney disease markers. Methods: Variables used to diagnose periodontitis were: (i) probing pocket depth (PPD), (ii) attachment loss (AL), (iii) bleeding on probing (BOP), (iv) plaque index (PI) and (v) extent and severity index. Blood and urine were collected from 60 apparently healthy non-smokers (men and women), consisting of a test group of 30 subjects with periodontitis (age 46±6 yrs) and a control group of 30 healthy subjects (age 43±5 yrs). Kidney function markers (urea, creatinine, uric acid and albumin contents) were measured in the serum and urine. Also, the glomerular filtration rate was estimated from creatinine clearance, from the abbreviated Modification of Diet in Renal Disease formula and from the albumin: creatinine ratio in a 24-h sample of urine. Results: It was found that the control group had a greater mean number of teeth than the test group and that the two groups also differed in PPD, AL, BOP and PI, all these variables being higher in the test group (P=0.006). For the extent and severity index of both PPD and AL, the test group had much higher medians of both extent and severity than the control group (P=0.001). With regard to kidney function, none of the markers revealed a significant difference between the control and test groups and all measured values fell within the reference intervals. Conclusions: It is proposed that severe periodontitis is not associated with any alteration in kidney function.
Keywords: Albumin; Creatinine clearance; Kidney function markers; Urea; Uric acid